Campaign contributions, policy decisions, and election outcomes: A study of the effects of campaign finance reform - Christopher Magee (Levy Economics Institute of Bard College, 2001)
Proposals for campaign finance reform are essentially based on the belief that political influence can be bought with financial donations to a candidate's campaign. But do contributions really influence the decisions of legislators once they are in office? In this brief, Christopher Magee examines the link between campaign donations and legislators' actions. His results suggest that political action committees donate campaign funds to challengers in order to affect the outcome of the election by increasing the challenger's chances of winning. These contributions have a large effect on the election outcome but do not seem to affect challengers' policy stances. In contrast, campaign contributions to incumbents do not raise their chances of being reelected and seem to be given with the hope of gaining influence.
Keywords: 330; Wahlkampffinanzierung; Reform; USA